Respons Pertumbuhan Dan Hasil Bibit Sebar F4 Isolat FP007 Jamur Merang (Volvariella volvaceae) Faperta UNSIKA Akibat Perbedaan Media Tumbuh - Ardhana, Felia; Lestari, Ani; Supriadi, Devie Rienzani (JURNAL AGROPLASMA, 2023)
Mushrooms are a food ingredient that is liked by the people of Indonesia and have a fairly high variety of species. Currently mushroom production in Indonesia is still experiencing unstable or fluctuating changes. The success of mushroom cultivation apart from proper cultivation techniques, straw mushroom requires a growing medium that can support its growth and production properly. This study aims to obtain culture media material that gives the best results for the growth of seedlings of F4 isolate FP007 straw mushroom (Volvariella Volvaceae). This experiment was conducted at a mushroom house owned by a farmer located in Pasirmulya Village, Majalaya District, Karawang Regency, carried out from March to May 2023. The research method used was an experimental method with a single factor Randomized Block Design (RBD) with 5 replications. There were 7 treatments, namely A (100% Straw), B (80% Straw + 20% Rice Husk), C (50% Straw + 50% Cotton), D (30% Straw + 20% Rice Husk + 50% Wood Powder ), E (25% straw + 75% sawdust), F (25% straw + 25% sawdust + 50% cotton), G (20% straw + 20% rice husk + 60% cotton). The effect of the treatment was analyzed by analysis of variance at the 5% level and then continued with the DMRT (Duncan Multiple Range Test) at the 5% level. The results showed that there was a significant effect of differences in growing media on the growth and yield of F4 seedling isolate FP007 mushroom (Volvariella volvaceae). Treatment G (20% Straw + 20% Rice Husk + 60% Cotton) gave the highest average fruit weight per plot of 6.30 g, the average harvest intensity of one growing season was 7.80 days and the total weight of one plot of 852 g, if the total weight is 71.58 kg.Â Key Words:F4 Faperta Unsika,Straw Mushroom, and Straw